Intersubjectivity, Joint Action and Sociality. Issue 3 (26th July 2022) - Cipolletta, Sabrina; Mascolo, Michael F.; Procter, Harry
Abstract: Intersubjectivity consists of the mutual coordination, incorporation and sharing of meaning and experience between people over time. The study of intersubjectivity raises difficult conceptual and methodological issues. Defined as a form of mutually coordinated experience, intersubjective processes are those that occur between rather than merely within persons. As such, the concept of intersubjectivity incorporates but extends beyond related concepts such as sociality, commonality, and perspective taking. To the extent that intersubjective processes are relational ones, their study requires the ability to analyze forms of engagement that occur between rather than merely within individual actors. We suggest that the most basic way to assess intersubjectivity involves recruiting the human capacity for intersubjective engagement itself as a primary method of psychological research. Toward this end, drawing on existing studies involving moment-by-moment observation of videotaped interaction, we track the developmental changes of different forms of intersubjective engagement as they occur between infants and their caregivers. Building on this work, we propose and illustrate methods for identifying moment-by-moment changes in sociality and intersubjective engagement as they occur in verbal and nonverbal joint action among adults.